Three approaches to multi-materiality through co-taught learning projects - Härkki, Tellervo; Vartiainen, Henriikka; Rönkkö, Marja-Leena (Oslo and Akershus University College, Learning Centre and Library, 2025)
This study examines the implementation of multi-material crafts in Finnish basic education from the viewpoint of utilizing co-teaching to enhance craft education. With the removal of gender-segregated craft subjects and the merger of textile and technical subjects into a common craft subject, room for new pedagogical strategies has emerged. The study involved 17 teachers who had participated in a national development program aimed at integrating multi-material and co-teaching methods into the learning process in crafts. Data were collected through interviews, focusing on how these teachers planned and executed multi-material craft projects in a co-teaching setup. The results showed that teachers adopted diverse approaches to multi-material crafts, depending on their pedagogical aims and the resources available. Three major categories of multi-material, co-taught learning projects were identified – fixed, teacher-directed, and open choice – each offering varying degrees of material and technological integration and pedagogical freedom. The study also found that newly acquired technological skills significantly influenced the roles and collaboration dynamics between co-teachers, positively affecting the division of labor and the overall teaching and learning experience.